Young onset dementia. Issue 7 (July 2016) - Draper, B.; Withall, A.
Abstract : Young onset dementia (YOD), where symptoms of dementia have an onset before the age of 65, has become more prominent due to the population increase from the Baby Boomer generation. This clinical perspective examines key issues in the assessment, diagnosis and management of YOD. Challenges in the assessment and diagnosis of YOD are partly due to the diverse range of types of YOD, where degenerative dementias are less common and secondary dementias more common than in late onset dementia. Early symptoms are broad and include depression, behavioural change, neurological disorders, systemic disorders and mild cognitive impairment (MCI). Perceived diagnostic delay may result in frustration and distress in people with YOD and their families. Chronic depression and MCI are associated with longer time to diagnosis, and in these situations, clinicians need to establish appropriate review processes and communicate clearly. A diagnosis of YOD may have marked consequences for a younger person, including early retirement, financial impacts and the psychological challenge of coming to grips with cognitive decline. Partners, children and other supporters often have unmet needs, feel burdened by care and are at high risk of physical and emotional consequences. Concerns about the heritability of dementia may add to family distress. Recent community service developments in Australia for YOD are outlined and the challenges of residential care described.